Pembuatan Pestisida Nabati dari Daun (Balakacida, Serai dan Sirsak) dengan Perbandingan Penambahan Surfaktan dan Tanpa Surfaktan - Dinda Amalia; Sariadi Sariadi; Zulkifli Zulkifli (Jurnal Teknologi, 2023)
Production of vegetable pesticides from leaves (lemongrass, balakacida, and soursop) with a ratio of surfactant addition and no surfactant is carried out by liquid-solid extraction. This research aims to influence the effect of the use of leaf types and the use of surfactants and without surfactants with differences in maceration time on the quality of the vegetable pesticides produced. The research method was carried out by maceration extraction which would release flavonoid compounds and a mortality test was carried out on black ants (Dolichoderus thoracicus). The research results obtained from the three raw materials, namely balakacida leaves with the addition of surfactant, were the best results which desired to achieve a lethal dose (LD 100) with all test ants dead, whereas, without the addition of surfactant, it only reached the middle lethal dose (LD 50). As the maceration time increases, the number of ant deaths increases. The characteristics of vegetable pesticides produced from flavonoid levels have a positive correlative relationship to the mortality of black ants (Dolichoderus thoracicus). So what was obtained in the test for flavonoid compounds produced an orange/yellow color and there were functional groups OH, C-H, N-O, N=C=S, and C=C.